Determinant of Micro, Small and Medium Enterprises on Taxpayer Compliance (An Empirical Study of MSME Coffee Shops in Tanggerang Selatan, Indonesia) - Amanda Hafidzia Azhari; Eva Herianti; Septi Wulandari Chairina (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
This study aims to analyze the effect of tax literacy, The application accounting, modernization of tax administration systems, and taxpayer awareness on micro, small and medium enterprise (MSME) taxpayer compliance. This research is quantitative using primary data obtained by distributing questionnaires to MSME coffee shops taxpayers in South Tangerang city in West Java,Indonesia. In this study, the sampling process used a convenience sampling method according to the theory Roscoe formula which covered 50 respondents. The collected data was then analysed with SEM Partial Least Square method using SmartPLS (version 3.2.9). The results of this study indicate that tax literacy, application accounting, modernization of tax administration system and taxpayer awareness have a significant effect on MSME taxpayer compliance. has a significant effect on MSME taxpayer compliance.